Health and Safety in Canadian Workplaces - Foster, Jason; Barnetson, Bob (Open textbook library., 2016)
Workplace injuries happen every day and can profoundly affect workers, their families, and the communities they live in. This textbook provides workers with an introduction to effective injury prevention. The book pays particular attention to how issues of precarious employment, gender, and ill health can be better handled in Canadian occupational health and safety (OHS).This introduction to OHS differs from others because it contends that the practice of occupational health and safety can only be properly understood if we acknowledge that workers and employers have conflicting interests. Specifically, we investigate which workplace hazards are recognized and controlled,the manner in which these hazards are controlled, and who makes these decisions. These are all factors that reflect the broader political economy of employment and suggest that OHS is contested terrain.